FeedMe - a semantic RSS aggregator - Ljubešić, Nikola, informatičar; Cimperšak, Mislav; Tkalec, Marija; Boras, Damir (2010)
We demonstrated a system for semantic aggregation of RSS feeds. For aggregation the system uses the event detection algorithm developed in Ljubešić's PhD thesis "Event detection in parallel information sources" (2009). The system enables the user to choose RSS feeds that should be semantically aggregated as well as two ways of filtering the feeds by affirming or negating the content of specific RSS feeds.
Projekt MZOS
ENG